INTERSTITIAL LUNG DISEASE IN COMMON VARIABLE IMMUNE DEFICIENCY. (February 2015) - Richards, Stephanie; Robertson, Colin; Chow, C. W.; Choo, Sharon
Abstract : The clinical and immunological phenotype of common variable immune deficiency (CVID) is heterogeneous. Here we describe a case of possible CVID, with associated interstitial lung disease. A 5½-year-old non-consanguineous Caucasian male initially presented with an episode of severe acute hepatitis of unclear aetiology, which resolved without treatment. Six weeks later he developed progressive sub-acute respiratory failure. CT chest and lung biopsy were consistent with non-specific interstitial pneumonitis. Immune investigations were unremarkable apart from mild memory B cell lymphopenia. Subsequent investigations over the next year demonstrated progressive B cell, memory B cell and CD8+ T cell lymphopenia, decreasing IgG and IgM, and a good antibody response to Pneumovax immunisation. The proportion of regulatory T cells (CD3+/CD4+/CD25++/CD127–) was reduced. Although there was a good response to pulse methylprednisolone, respiratory symptoms returned and soluble CD25 levels (sCD25) increased as prednisolone was weaned, despite addition of mycophenolate. Rituximab and immunoglobulin replacement were commenced, with stabilisation of symptoms and decrease in sCD25. Several discussion points arise from this case, including the clinical and laboratory phenotype of CVID with interstitial lung disease, and management of these patients. Identification of molecular defects affecting co-stimulation would facilitate consideration of alternative treatments in these patients.